Prevalence of HBsAg positive among non- immunized junior high school students in Bandung - Lia Marlia K.; Yasmar Alfa; Iesje Martiza; Dwi Prasetyo (Indonesian Pediatric Society Publishing House, 2016)
Background Sero-epidemiologic survey of hepatitis B is used to determine the prevalence of hepatitis B infection in community, particularly among population which has not been covered by hepatitis B immunization program. Objective To determine the prevalence of HBsAg positive among junior high school's students in Bandung. Methods A cross-sectional study was conducted on junior high school (SMP) students. Subjects were selected randomly using stratified cluster sampling of 4 junior high schools in Bandung. The inclusion criteria were students of first and second grade, lived in Bandung area, without history of hepatitis B immunization. Subjects were interviewed and were screened for HBsAg using Reverse Passive Hemagglutination technique. Results There were 341 subjects consisted of 201 girls and 140 boys. None of the subjects had any sexual intercourse or intravenous drugs, while 261 subjects (76.5%) had shared personal care. History of blood transfusion was found in 13 subjects (3.8%), tattooing in 2 (3.8%), body piercing in 28 (8.2%), and contact with chronic liver disease patients in 16 (4.7%). Based on HBsAg serologic test, 3 subjects (2 boys and 1 girl) were found to be positive, thus HBsAg positive prevalence was 0.9% (95%CI -0.001;0.019). Two of them had shared personal care with their relatives or friends. None of them had tattoo, body pierce, blood transfusion, or contact with chronic liver disease patients. Their physical condition were within normal limit. One of them refused to do further laboratory tests because no permission from his parents. Liver function of those students were normal, anti-HBc IgM were negative, and total anti- HBc were positive in two of them. Conclusion The prevalence of HBsAg positive in junior high school students in Bandung is low and there is no obvious risk factor for the transmission of the disease.